Implementation of Character Educ Implementasi Pendidikan Karakter melalui Semarbowo di SDN Tambakaji 03 Kota Semarang - Rahmawati, Yuniar; Witanto, Yuli (Universitas Veteran Bangun Nusantara, 2024)
This study aims to describe the implementation of character education through Semarbowo at SDN Tambakaji 03 and its problems. The research method is descriptive qualitative. Data analysis includes four flows, namely data collection, data reduction, data presentation, and conclusion drawing. Data were collected through observation, interviews, and documentation. Primary data sources are fifth grade teachers and principals and secondary data sources are fifth grade students of SDN Tambakaji 03. The results showed how to implement character education through Semarbowo, among others: 1) communicating using Javanese language by all school members every Thursday, 2) kissing the hands of teachers at the school gate while saying